How leaders' bias tendency affects employees' knowledge hiding behavior: The mediating role of workplace marginalization perception - Du, Sijin; Xie, Wenli; Wang, Jianjun (Frontiers in Psychology, 2022)
Employees' knowledge hiding behavior has a essential inhibitory impact on organizational innovation and employee knowledge sharing. Accordingly, studying the antecedents and influencing mechanisms of employees' knowledge hiding behavior is quite necessary. In the perspective of leader-member exchange theory and resource conservation theory, the leaders' bias tendency will lead to the workplace marginalization perception of some employees and promote the generation of employees' knowledge hiding behavior. Thus, this research is intended to discuss the influence of leaders' bias tendency toward employees' knowledge hiding behavior, and to analyze the mediating effects of employees' perception of workplace marginalization and the moderating role of emotional commitment to the organization. The sample of this study covered 500 Chinese full-time corporate employees. The conclusions of the research indicate that: (1) Leaders' bias tendency is vitally and absolutely correlated with employees' knowledge hiding behavior; (2) Workplace marginalization perception plays an intermediary role between Leaders' bias tendency and employees' knowledge hiding behavior; (3)Emotional commitment to the organization plays a negative moderating role between Leaders' bias tendency and employees' knowledge hiding behavior; (4)Emotional commitment to the organization plays a negative moderating role between workplace marginalization perception and employees' knowledge hiding behavior.These findings will help organizations and managers to recognize the harm of bias tendency, regulate their own behaviors, and effectively reduce the generation of employees' knowledge hiding behaviors, thereby promoting knowledge sharing and innovative behaviors in organizations.